BIBLIOMETRIC ANALYSIS ON AUDITOR PERFORMANCE RESEARCH - Izzatul Jannah; Rindang Widuri (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
Auditor performance is a general topic that has been extensively researched worldwide. However, of course, some aspects are still minimally discussed in previous research. Therefore, this study applied a bibliometric analysis to find out the overall picture and aspects or matters that were still rarely discussed about auditor performance. The data source is obtained from Scopus with a publication time span of 2013-2022 and the keyword "Auditor Performance". The number of studies that became the data in this study was 506 studies. These data were analyzed using the VOS Viewer software. Based on the results of the bibliometric analysis, it is concluded that the variable or aspect that has been widely studied in the auditor's performance keyword is audit quality. Then, the aspect or variable that can be a novelty idea is big data. Further researchers can explore or discuss more deeply related to big data and its relationship to auditor performance.